Emerging therapeutic modalities for acute myeloid leukemia (AML) in older adults. Issue 6 (November 2017) - Huang, Li-Wen; Olin, Rebecca L.
Abstract: Treatment for the older adult with acute myeloid leukemia (AML) is challenging, due to both more aggressive disease biology as well as patient-related risk factors that limit tolerance of intensive chemotherapy. The use of prognostic models and comprehensive geriatric assessments can help hematologists evaluate the suitability of intensive chemotherapy for individual patients. For older patients considered fit for intensive chemotherapy, standard induction therapy should be given, followed by consideration of reduced intensity allogeneic stem cell transplantation. Patients considered unfit for intensive therapy are standardly treated with hypomethylating agents. Several new therapeutic agents have shown promising results either by improving intensive chemotherapy (CPX-351), by improving upon lower intensity therapy (venetoclax, antibody drug conjugates), or by targeting somatic mutations (FLT3 inhibitors and others).